Problem Based Learning E-Module for Facilitating Sociology Learning in the Digital Era - Yuningtyas, Laras Andita; Sariyatun; Djono (Jurnal Edutech Undiksha, 2023)
This Technological developments present a variety of digital learning resource options that can be used by teachers, as well as being a solution to overcome the problem of less interactive learning. This study aims to develop a problem-based learning e-module product for sociology learning in senior high schools. This research approach is research and development (RnD), which adopts the 4-D model. This research will involve two media experts, two material experts, and three subject teachers. Data collection techniques use non-test techniques with instruments consisting of questionnaires. Obtaining questionnaire scores will be analyzed descriptively with percentages. The results of this study indicate that problem-based learning-based e-modules obtain a percentage score of 91% from media experts and are included in the 'very good' qualification. The assessment of material experts obtained 86%, which was included in the qualification of 'very good. The teacher's assessment is 89% which is included in the 'very good' category. The e-module developed in this study was deemed 'very feasible' to be used as a learning medium and tested on students in the sociology learning process.